Religion (Islam) And Politics; Analysis Discussion - Indar Arifin (Jurnal Ad'ministrare, 2021)
This research is a literature study that discusses and analyzes the relationship between religion and politics from the historical aspect, the development of religion in the political realm as well as the discourse between the two things. Philological analysis is used to determine the extent of the relationship between political theory and religious belief, in this case Islam. The results of the analysis illustrate that religion as the basis for political morals is no longer used as it should, but only becomes a tool to win power. In that context, the people of the State have presented themselves as an organized mass, and they are not aware that a structural crime (made in such a way) has happened to them, they are given little pleasure while others who win the power take more benefits from the State. they. Political violence has actually occurred wrapped in a certain ideology or religion, and its legitimacy has been very well tested, especially if the legitimacy is obtained through instruments under the political democratic system through general elections. General elections become a very significant relationship with the legitimacy of political power.